Microfungal 'Weeds' in the Leafcutter Ant Symbiosis - Rodrigues, A. [UNESP]; Bacci Junior, Mauricio [UNESP]; Mueller, U. G.; Ortiz, A.; Pagnocca, Fernando Carlos [UNESP] (Springer, 2008)
Leafcutter ants (Formicidae: tribe Attini) are well-known insects that cultivate basidiomycete fungi (Agaricales: Lepiotaceae) as their principal food. Fungus gardens are monocultures of a single cultivar strain, but they also harbor a diverse assemblage of additional microbes with largely unknown roles in the symbiosis. Cultivar-attacking microfungi in the genus Escovopsis are specialized parasites found only in association with attine gardens. Evolutionary theory predicts that the low genetic diversity in monocultures should render ant gardens susceptible to a wide range of diseases, and additional parasites with roles similar to that of Escovopsis are expected to exist. We profiled the diversity of cultivable microfungi found in 37 nests from ten Acromyrmex species from Southern Brazil and compared this diversity to published surveys. Our study revealed a total of 85 microfungal strains. Fusarium oxysporum and Escovopsis were the predominant species in the surveyed gardens, infecting 40.5% and 27% of the nests, respectively. No specific relationship existed regarding microfungal species and ant-host species, ant substrate preference (dicot versus grass) or nesting habit. Molecular data indicated high genetic diversity among Escovopsis isolates. In contrast to the garden parasite, F. oxysporum strains are not specific parasites of the cultivated fungus because strains isolated from attine gardens have similar counterparts found in the environment. Overall, the survey indicates that saprophytic microfungi are prevalent in South American leafcutter ants. We discuss the antagonistic potential of these microorganisms as weeds in the ant-fungus symbiosis.